2003
DOI: 10.1111/1468-232x.00301
|View full text |Cite
|
Sign up to set email alerts
|

Do Public‐Sector Strike Bans Really Prevent Conflict?

Abstract: This article examines the effectiveness of strike-ban laws in reducing industrial conflict at the municipal level of government. Our central findings are that job actions were higher in states that had no law or no finality in the law, publicity campaigns were used as a pressure tactic in the bargaining process, and grievance delays were greatest under final offer arbitration. Thus dispute costs are highest in jurisdictions that provide no finality in dispute resolution whether or not an explicit framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…This is surprising, since many observers argue that the legislative framework strongly influences the level and pattern of strikes. In the USA, for example, public-sector strike bans have been shown to have significant damping effects (Hebdon and Stern, 2003). Yet in Europe, if the workers wish to strike, the specific national institutional rules are apparently of little significance.…”
Section: The 'Many Cases Of Europe'mentioning
confidence: 99%
“…This is surprising, since many observers argue that the legislative framework strongly influences the level and pattern of strikes. In the USA, for example, public-sector strike bans have been shown to have significant damping effects (Hebdon and Stern, 2003). Yet in Europe, if the workers wish to strike, the specific national institutional rules are apparently of little significance.…”
Section: The 'Many Cases Of Europe'mentioning
confidence: 99%
“…L'arbitrage n'est pas la seule option offerte au lieu du recours à la grève chez les employés du secteur public. Par exemple, aux États-Unis, la plupart des conflits dans le secteur public se terminent par une sorte de commission d'enquête ou par une médiation qui ne lie pas les parties (Hebdon et Stern 2003). Au Canada, le dernier recours, lorsque l'impasse persiste, consiste soit à offrir un droit limité à la grève, soit à recourir à l'imposition de l'arbitrage obligatoire, ou bien le choix entre l'arbitrage ou le recours à la grève (Adell, Grant et Ponak 2001).…”
Section: Discussionunclassified
“…There is mounting evidence, for example, of a higher number of grievances and grievance arbitrations under no-strike laws in Ontario and the U.S. municipal sector (Hebdon andStern 1998, 2003). Hebdon and Stern (2003) also found that arbitration laws had no effect in reducing strikes or job actions (e.g., sickouts, slowdowns, working-to-rule actions, and wildcat walkouts). Moreover, job actions levels and union political activity were found to be higher under states with final offer arbitration 2 as the final step.…”
Section: Industrial Conflict and Strikesmentioning
confidence: 97%
See 1 more Smart Citation
“…Hebdon and Mazerolle (2003) found that mandatory arbitration led to an increase in employer-employee impasses at the bargaining table as high as 21 percent of the time relative to workers with the right to strike. They also found that while strike-ban legislation is probably successful in reducing the likelihood of strikes, it increases the likelihood of other types of disputes, such as work-torule situations or work slowdowns (see also Hebdon and Stern 2003).…”
Section: The Unintended Consequence Of Banning and Ending Strikesmentioning
confidence: 98%